1979
DOI: 10.1007/bf02660074
|View full text |Cite
|
Sign up to set email alerts
|

Study of the thermooxidative behavior of edible oils by thermal analysis

Abstract: The complex thermoanalytical investigation of oil stability has been made by means of the Derivato‐graph using dynamic and static programs. TG, DTG and DTA curves have been registered simultaneously. The aim of the experiments was to determine the optimum conditions for examination of oxidative stability and oxidation state of edible oils. Results show that the study of thermal decomposition under dynamic conditions allows the detection of thermal and oxidative degradation. Storability can be investigated unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Santos et al [21] observed a relation between mass loss of saturated fatty acids and TG/DTG data of commercial vegetable oils (among them olive oil), attributing the first step to the thermal decomposition of the most unsaturated fatty acids moieties, whereas the second and the third were related to the monosaturated and saturated fatty acid decomposition, respectively. On the contrary, the last decomposition step related to the oxidation of the carbonaceous residue was attributed by other authors [22,23]. Garcia et al [24] related the first and the second mass loss steps of TG/DTG curves to the oxidation of unsaturated and saturated fatty acids, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Santos et al [21] observed a relation between mass loss of saturated fatty acids and TG/DTG data of commercial vegetable oils (among them olive oil), attributing the first step to the thermal decomposition of the most unsaturated fatty acids moieties, whereas the second and the third were related to the monosaturated and saturated fatty acid decomposition, respectively. On the contrary, the last decomposition step related to the oxidation of the carbonaceous residue was attributed by other authors [22,23]. Garcia et al [24] related the first and the second mass loss steps of TG/DTG curves to the oxidation of unsaturated and saturated fatty acids, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Surprisingly, we have encountered only a few papers dealing with DSC or DTA study of the oxidation of oils or fats (9)(10)(11)(12)(13)(14). To our knowledge, no paper has been published on the thermoanalytical study of biodiesel fuels.…”
mentioning
confidence: 81%
“…Figure 1 shows that, within range of 80-320°C, the nonisothermal DSC oxidation of the oils occurs in two stages. The first stage is decisive for the study of oxidative changes, the second stage corresponds to quantitative decomposition of the oils (8,9). The kinetic parameters describing the induction period have been obtained for nonisothermal DSC measurements and isothermal Oxidograph measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, if the oxygen concentration in the oil is lower than the saturation concentration, IP can be expressed as [7] where t i o is the IP length for the saturated oxygen concentration in the oil. From Equation 1 it follows: [8] Combination of Equations 7 and 8 gives [9] where B o is the kinetic parameter B for the saturated oxygen concentration in the oil and E d and E a are the activation energies for the diffusion and the oxidation processes occurring during the induction period. From Equation 9 we see that the parameters B and B o are close for the conditions D → ∞, (S/V) → ∞, z → 0, and k → 0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation